Projection structure of the cytochrome bo ubiquinol oxidase from Escherichia coli at 6 A resolution. - Gohlke, U (1997)
The haem-copper cytochrome oxidases are terminal catalysts of the respiratory chains in aerobic organisms. These integral membrane protein complexes catalyse the reduction of molecular oxygen to water and utilize the free energy of this reaction to generate a transmembrane proton gradient. Quinol oxidase complexes such as the Escherichia coli cytochrome bo belong to this superfamily. To elucidate the similarities as well as differences between ubiquinol and cytochrome c oxidases, we have analysed two-dimensional crystals of cytochrome bo by cryo-electron microscopy. The crystals diffract beyond 5 A. A projection map was calculated to a resolution of 6 A. All four subunits can be identified and single alpha-helices are resolved within the density for the protein complex. The comparison with the three-dimensional structure of cytochrome c oxidase shows the clear structural similarity within the common functional core surrounding the metal-binding sites in subunit I. It also indicates subtle differences which are due to the distinct subunit composition. This study can be extended to a three-dimensional structure analysis of the quinol oxidase complex by electron image processing of tilted crystals.